Rhétoriques contemporaines de la paternité. Le cas de Chevillard - Maziarczyk, Anna (Romanica Silesiana)
Finding new forms for a literary representation of the father is a challenge, as family relations constitute one of the most popular literary motifs. Éric Chevillard’s innovative presentation of this subject takes the form of an unconventional blog, which is more literary than personal, and which exists in electronic and print formats. This peculiar – half-fictional, halfautobiographical – diary tells the story of a “housewriter,” combining creative pursuits with everyday fatherly duties, and thus invites the reader to reflect on the father–daughter relation and the changes it is undergoing in our times.